3D crustal and lithospheric model of the Arabia–Eurasia collision zone. (15th May 2016) - Motavalli-Anbaran, Seyed-Hani; Zeyen, Hermann; Jamasb, Ali
Highlights: Crustal and lithospheric model of the Arabia–Eurasia collision zone. We constructed a new model of Moho depths and lithospheric thickness. The base of the lithosphere shows strong upwelling under all of Eastern Anatolia. Abstract: Three-dimensional joined inversion of topography, gravity and geoid data was carried out in the collision zone between the Eurasian and Arabian plates, comprising Central and Eastern Anatolia, the Black Sea Basin and the Caucasus region. The 3D algorithm, first introduced by Motavalli-Anbaran et al. (2013), is based on a Bayesian approach with Gaussian density functions in which the targeted area is divided into vertical columns, each comprised of four layers namely water (of known thickness i.e. bathymetry) if present, crust, lithospheric mantle, and asthenosphere. The inversion results are Moho depth, average crustal density and depth to the lithosphere–asthenosphere boundary, defined here as the 1350 °C isotherm. Existing seismic Moho depths were used as a priori information in order to constrain crustal thicknesses. Thickest crust (up to 50 km) was found underneath the Great Caucasus Mountains, thinnest crust (22–25 km) underneath the Black Sea Basin. The East-Anatolian plateau is underlain by relatively thick crust (up to 45 km), thinning to less than 40 km towards the Central Anatolian Plateau. Eastern Anatolia and the eastern part of Central Anatolia are underlain by strongly thinned lithosphere (up to 100 km). Thickest lithosphere (up to 200 km) underlies the Caspian Basin and the Russian Platform.